Silent city - Davis-Goff, Sarah (Flatiron Books, 2023)
"Outside the walls of Phoenix City, where the plague has overrun Ireland, one bite from the savage skrake means death or infection. Inside, Orpen and the other survivors of the plague gather in meager numbers. They are protected from disease and death, but the city is by no means a refuge. Phoenix City is ruled with an oppressive hand, with even the best of the leadership power hungry and ruthless. Orpen and the banshees--a fierce, all-women force of fighters--keep the peace, or shatter it, depending on their orders. But when two women are publicly executed, Orpen knows she must make a choice between guaranteed survival within a cruel society or treacherous freedom beyond the walls. A story of friendship, justice, and belonging, Silent City is a feminist, voice-driven take on leadership in dire times"--